Cold War spy satellite images reveal long-term declines of a philopatric keystone species in response to cropland expansion - Catalina Munteanu; Johannes Kamp; Mihai Daniel Nita; Nadja Klein; Benjamin M. Kraemer; Daniel Müller; Alyona Koshkina; Alexander V. Prishchepov; Tobias Kuemmerle (Proceedings of the Royal Society B: Biological Sciences, 2020)
Agricultural expansion drives biodiversity loss globally, but impact assessments are biased towards recent time periods. This can lead to a gross underestimation of species declines in response to habitat loss, especially when species declines are gradual and occur over long time periods. Using Cold War spy satellite images (Corona), we show that a grassland keystone species, the bobak marmot (Marmota bobak), continues to respond to agricultural expansion that happened more than 50 years ago. Although burrow densities of the bobak marmot today are highest in croplands, densities declined most strongly in areas that were persistently used as croplands since the 1960s. This response to historical agricultural conversion spans roughly eight marmot generations and suggests the longest recorded response of a mammal species to agricultural expansion. We also found evidence for remarkable philopatry: nearly half of all burrows retained their exact location since the 1960s, and this was most pronounced in grasslands. Our results stress the need for farsighted decisions, because contemporary land management will affect biodiversity decades into the future. Finally, our work pioneers the use of Corona historical Cold War spy satellite imagery for ecology. This vastly underused global remote sensing resource provides a unique opportunity to expand the time horizon of broad-scale ecological studies.
https://doi.org/10.6084/m9.figshare.c.4971176
Keywords: 330; long-term species decline; land-use change; burrowing mammal; agricultural conversion; Corona spy satellite imagery